EFFICIENCY OF HYDROTHERAPY ON THE FUNCTIONALITY OF CHILDREN WITH DUCHENNE MUSCULAR DYSTROPHY (REMUNOM, 2025)
Duchenne Muscular Dystrophy is more than just a diagnosis; it is a challenging reality that shapes the lives of children and their families, requiring resilience and innovation at every step. This hereditary genetic condition leads to progressive muscle degeneration, with an incidence of approximately 1 in every 3,500 boys, particularly affecting the muscles of the legs and pelvis. This results in difficulties walking, climbing stairs, running, and rising from the ground. The disease progresses in an ascending manner, also affecting respiratory muscles, the trunk, and upper limbs, ultimately necessitating the use of a wheelchair over time. The main symptoms usually appear in the early years of life and include unstable gait, calf hypertrophy, walking on tiptoes, and difficulties performing movements such as jumping and running. As the disease progresses, muscle degeneration affects breathing and further limits the patient's mobility. These symptoms typically arise in childhood, making early understanding and intervention essential. The daily challenges faced by these young individuals extend beyond mobility, impacting their social interactions, self-esteem, and emotional development. Families, in turn, become pillars of support, navigating therapies, medical consultations, and necessary home adaptations. In this scenario, physiotherapy emerges as a crucial ally, offering not only techniques to preserve muscle function but also strategies to improve quality of life. Through personalized exercises and therapeutic approaches, physiotherapists help maximize autonomy and well-being, providing hope and support. This research aims to describe what Duchenne Disease is, its impact on the lives of children, and the vital role that hydrotherapy plays in promoting quality of life and in the daily fight against the challenges imposed by the disease.